Karinganire Umutesi: capstone - Umutesi, Karinganire, artist (Colorado State University. Libraries, 2023)
The artist's statement: My name is Karinganire Umutesi, but I go by Umutesi. Growing up, I have always been interested in storytelling and business. I am a graphic designer, an illustrator, and a storyteller, and an entrepreneur who's also passionate about African Cultures. Growing up, I always found myself buying hundreds of sketchbooks and exploring my surroundings through drawing and illustration. What I love about Graphic Design is the power you get from it, for design can communicate to a large mass even if there are cultural, linguistic, or geographic differences. My goal is to use design as a gateway for people without a voice, to show their stories and their truth.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design